2019
DOI: 10.12669/pjms.36.icon-suppl.1718
|View full text |Cite
|
Sign up to set email alerts
|

The role of the poultry industry on kidney and genitourinary health in Pakistan

Abstract: Pakistan is experiencing a “double burden’’ of disease. Under-development is associated with illnesses like infections and nutritional deficiency, and is accompanied with diseases linked with development, such as diabetes, hypertension, cancer and chronic kidney disease. In Pakistan, renal and genitourinary diseases are an important, unaddressed health issues. Chronic kidney disease of unknown etiology (CKDu) is a recognized form of renal failure in Pakistan. A possible cause of CKDu is toxins such as arsenic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Also, diabetes and hypertension significantly contribute to CKD or end-stage kidney disease [ 18 , 21 , 22 ]. Specifically, in low-income countries, the significant reasons for CKD include diabetes mellitus (DM), hypertension (HTN), obesity, and cardiovascular disease [ 25 , 26 ]. This reveals an entanglement of numerous biosocial factors that make an individual prone to CKD.…”
Section: Chronic Kidney Disease (Ckd) and Diabetes In Pakistanmentioning
confidence: 99%
“…Also, diabetes and hypertension significantly contribute to CKD or end-stage kidney disease [ 18 , 21 , 22 ]. Specifically, in low-income countries, the significant reasons for CKD include diabetes mellitus (DM), hypertension (HTN), obesity, and cardiovascular disease [ 25 , 26 ]. This reveals an entanglement of numerous biosocial factors that make an individual prone to CKD.…”
Section: Chronic Kidney Disease (Ckd) and Diabetes In Pakistanmentioning
confidence: 99%
“…There is debate about its etiology as it is caused by heat stress and water depletion leads to acute tubular injury or overhydration of contaminated water with heavy metals or pesticides causing tubulointerstitial disease. In a review of water content in different areas of Pakistan Salman et al found a high level of arsenic, ochratoxin, and Zearalenone in areas related to the chicken industry (28). Similarly, in a biopsy series, Ruqaya, and Salman et al found a high prevalence of tubulointerstitial disease in people belonging to these areas (29) Renal stones are prevalent in this area for this it is recognized as "stone belt".…”
Section: Ckd Causesmentioning
confidence: 99%